Loto glareosí- Rumicetun¡ gallaeciel, a new comnmnaity of the cliffs of Cabo Orlegal ancl A Capelada (Galicia, NW ofIhe Iberian Peninsula)Loto glareosí- Rumicetun¡ gallaeciel, a new comnmnaity of the cliffs of Cabo Orlegal ancl A Capelada (Galicia, NW ofI - Soñora, Xavier; Rodríguez-oubiña, Juan; Ortiz, Santiago (Botanica Complutensis, 1996)
ROoRiGtJEz-OmJBIÑA, J.; SOÑORA, E X. & Omníz, 5. Laco glareasi-Ramicetum gallaecici, a new community of tbe cliffs of Cabo Ortega> and A (`apelada (Galicia, NW of the Iberian Peninsula). Bat. (`omplacensis 21: ¡ ¡3-120. In this paper we report a study of the vegetatinía of serees on the cliffs of Ube A Capelada peninsula in the nortb coast of Galicia, following the rnethods of Ube Zúrich-Montpellier School. A new assocíatíon, Lara glarecsi-Ramicetam gallaecic¿ is proposed and its physiognomnic, syotaxonommc, biogeograpbical and ecological characteristics are described,